The Smartphone Dilemma in Early Childhood Education: Mitigating Negative Socio-Emotional Dynamics through Cooperative Play - Nuzul Imamiyah; Eny Nur Aisyah; Zhumakadyrova Nagima Shailobekovna (Journal of Psychological Insight, 2026)
The increasing use of smartphones among young children has raised concerns regarding their influence on social behaviour and emotional development in early childhood learning contexts. This study aims to explore how smartphone exposure shapes children’s social interactions and emotional responses in educational settings. A qualitative descriptive approach was employed involving early childhood learners, teachers, and parents as participants, with data collected through classroom observations, semi-structured interviews, and document review. The findings indicate that frequent smartphone exposure tends to reduce peer interaction, shorten attention spans during learning activities, and trigger more impulsive emotional reactions when children are separated from their devices. However, structured classroom strategies such as cooperative play, storytelling, and guided group activities were found to help restore social engagement and improve emotional responsiveness. The study contributes by providing contextual evidence on how digital exposure influences early childhood socio-emotional dynamics. These findings suggest the importance of balanced smartphone use and active parental–teacher supervision to support healthier developmental outcomes.